(untitled) (Baghdad Science Journal, 2014)
This research evaluated the effect of (UV)(400-320A)Hz(320-220B)Hz on the patient with vitiligo , using it with our new combing therapy that include the oral (Psorlene ) topical , meladinine solution applied on the Vitiligiousns Lesions , In edition to the instralesnional injection in the Vitiligiousns Lesions by long acting steroid (kenacort-A ) by aprecentage of (5%) , after that we expose the patient to UV . The ruslets of this way of treatment more effective by using of the UV rays in the treatment of vitiligo , while the previous treatment that used the UV ray with or with out the psorlene , the results were not effective on controlling of the Vitiligio diseases comparing by the treatment used in this research as it stop’s the spread of the diseases and curing it .